PROSPECTS AND PROBLEMS OF DEVELOPMENT OF CASPIAN REGION - R. K. Sabirova; С. А. Kirdasinova; Е. М. Аdiyetova; K. М. Utepkalieva; Т. Т. Tsatkhlanova (Scientific Journal of Pedagogy and Economics, 2019)
In the Republic of Kazakhstan, the development of the oil and gas sector is one of the most important branches of the national economy, which has its own historical roots and traditions, in connection with that, it is possible to trace the patterns and features of the functioning of the national economy. The article has a literature review conducted by Kazakhstani and foreign authors, which had a research on the issues of economic and environmental development of the national economy, including the oil and gas complex in various aspects. The article explores one of the topical issues of Kazakhstan’s economy - prospects and problems of development of the western region. The characteristic features of modern management processes in the field of industry development are shown. The authors of the article conducted a study of the oil and gas industry in Kazakhstan as a component of the national economy, there is analyzed the current state of the industry, taking into account the innovative processes taking place in the development of the region. As a result of the studies, the theoretical and methodological aspects of the development of the oil and gas complex are systematized, on the basis of which conclusions are drawn.